Pengaruh Carbon Emission Disclosure, Carbon Performance, dan Green Intellectual Capital Terhadap Kinerja Keuangan Perusahaan - Willy Sri Yuliandhari; Rezma Aulia Ramadhanty (AKUNTANSI 45, 2024)
This study analyzes the effect of carbon emission disclosure, carbon performance, and green intellectual capital on the financial performance of companies in the mining sector listed on the Indonesia Stock Exchange (IDX) in the period 2018-2022. Using a purposive sampling method, 8 companies with 40 observations were selected, but three data contained outliers, resulting in 37 observations. The results of descriptive statistical analysis and panel models with Eviews version 12 show that simultaneously, the three factors have a significant effect on the company's financial performance. Partially, carbon emission disclosure has a significant negative effect on financial performance, while carbon performance and green intellectual capital have a significant positive effect. This study suggests that companies improve carbon performance and green intellectual capital in order to strengthen relationships with the community or investors, which in turn can improve financial performance.